Characteristics and Sources of VOCs Emission during the O3 Pollution Prone Season in an Industrial City in Eastern China - Wenjuan Li; Qiongjing Mao; Genying Wu; Jian Wu (Aerosol and Air Quality Research)
Abstract To further illuminate the issue of coexisting PM2.5 and O3 pollution of the industrial city in China, this study carried out online observation of the concentrations and components of volatile organic compounds (VOCs) in Shaoxing in Zhejiang Province during the season prone to O3 pollution. The objective was to elucidate the emission characteristics and causative factors of VOCs—a shared precursor of both PM2.5 and O3—as well as to assess the ozone formation potential (OFP) and dissect the regional transfer and local sources. Over the observation period, the mean volume concentration of VOCs was 169.96 ppb. Halogenated hydrocarbon, alkane and benzene compounds predominated, representing 31.68%, 30.36%, and 23.32% of the total VOCs concentration, respectively. The mean OFP of VOCs was 849.75 µg m−3, with benzene compounds, alkene, ketone and alkane being the chief contributors, accounting for 41.62%, 25.81%, 11.48%, and 10.43% to the total OFP, respectively. Key reactive species included isoprene, m/p-xylene, toluene, 2-pentanone, n-butanal, o-xylene, ethylbenzene, methylvinvl ketone, 2,4-dimethylpentane and ethylene. Source apportionment analyses revealed that 46.26% of VOCs originated from neighboring provinces outside of Zhejiang Province, while contributions from other cities within Zhejiang Province, excluding Shaoxing, summed up to 36.05%. Conversely, Shaoxing’s local emissions constituted 17.69%. Among local sources, industrial process dominated at 64.51%, followed by solvent usage at 25.69% and mobile exhaust at 4.53%.